Synthesis and Reactions of PdII Complexes with Aryl, Aroyl, and Iminoaroyl Ligands – Insertion of CO and RNC into the Pd–Ar Bond and Intermolecular Coupling of the Ligands. Issue 3 (15th December 2014) - Suzaki, Yuji; Shirokawa, Masanori; Yagyu, Takeyoshi; Osakada, Kohtaro
Abstract: The arylpalladium(II) complexes [PdIAr(bpy)] (Ar = Ph, C6 H3 ‐3, 5‐Me2, C6 H4 ‐4‐OMe, C6 H4 ‐2‐OMe, C6 H4 ‐4‐C6 H4 ‐4‐I, 1‐naphthyl; bpy = 2, 2′‐bipyridine) undergo insertion of CO and CNR (R = t Bu, C6 H3 ‐2, 6‐Me2 ) into the Pd–aryl bond to produce [PdI(COAr)(bpy)] and [PdIC(=N–R)Ar(bpy)]. The dinuclear complex [C6 H3 ‐3, 5‐(OCH2 CH2 )2 C6 H4 ‐3‐PdI(bpy)2 ] is synthesized by the oxidative addition reaction of 1, 3‐bis[(3‐iodophenyl)‐1, 4, 7‐trioxaheptyl]benzene to [Pd(dba)2 ] (dba = dibenzylideneacetone). The addition of AgBF4 to the arylpalladium(II) complexes [PdIAr(bpy)] (Ar = C6 H4 ‐4‐OMe, C6 H4 ‐2‐OMe, 1‐naphthyl) produces the intermolecular coupling products of the aryl ligands, Ar–Ar. The reactions of AgBF4 with the aroylpalladium(II) complexes [PdI(COAr)(bpy)] (Ar = C6 H3 ‐3, 5‐Me2, C6 H4 ‐2‐OMe) result in decarbonylation and intermolecular coupling of the ligands to yield the diarylketones. The iminoaroylpalladium(II) complex [PdIC(=N t Bu)C6 H3 ‐3, 5‐Me2 (bpy)] undergoes hydrolysis of the ligand to yield t BuNHCO(C6 H3 ‐3, 5‐Me2 ). The addition of AgBF4 to the dinuclear complex [C6 H3 ‐3, 5‐(OCH2 CH2 )2 C6 H4 ‐3‐PdI(bpy)2 ] yields a mixture of the cyclic oligomers cyclo ‐[C6 H3 ‐3, 5‐(OCH2 CH2 )2 C6 H4 ‐3‐2 ] n ( n = 1–4) by inter‐ and intramolecular coupling of the aryl ligands. Abstract : Aryl‐, aroyl‐, and iminoaroyl iodidopalladium(II) complexes with a 2, 2′‐bipyridine ligand react with AgBF4 and H2 O to afford biaryls, diarylketones, and arylamides by labilization of the iodido ligand.